Sequential Use of Hemadsorption Using Cytosorb® and Biosky® Filter-Technology in A COVID-19 Patient Suffering from Severe ARDS - Mezger, Matthias; Eitel, Ingo; Ensminger, Stephan; Pogorzalek, Dirk; Huang, Zhipan; Graf, Tobias (Archives of Clinical and Medical Case Reports, 2020)
In March 2020, the World Health Organization (WHO) declared the novel coronavirus disease (COVID-19) pandemic. Here, we present the case of a patient who was admitted to our hospital with acute respiratory distress syndrome (ARDS) following infection with COVID-19. After initial stabilization through restrictive fluid management, hemadsorption using Cytosorb? was performed and finally temporary extubation of the patient was possible. However, the patient again clinically deteriorated and needed ventilation and finally veno-venous (VV) extracorporeal membrane oxygenator (ECMO) -support and high catecholamine application. Whilst being on VVECMO, hemadsorption using Biosky? filter was performed. In this manuscript, after a brief overview of the role of hemadsorption in ARDS, a detailed case presentation is followed by a critical discussion of the current literature.